Optimal operation of multi-energy systems - Ren, Xuejing (2019)
With the overexploitation of the fossil fuel, there is an urgent need to find a cleaner and efficient method to generate power. In electric power industry, integrated energy generation is considered as a method that are more efficient and environmental friendly. The close relation between different energy such as power, gas, wind and solar energy make the combination of these energies in a system become possible. In this project, an optimal operation dispatch of the micro-grid with IEEE33 bus network system combined with renewable energy (RE) and power to gas (P2G) technology is proposed. The system presented in this project comprised different energy sources and energy conversion devices. The objective function is the minimum of total cost. In this optimization problem, linear programming and software MATLAB are used to search for the best answer. The solving method is applied to two case study, the system with P2G process and without it. The results of simulation demonstrates that the proposed multi-energy system is more effective and environment-friendly. This power generation method can be considered as a promising way to tackle environment problem, therefore it deserves further research.